Inhibition of T-cell receptor beta-chain gene rearrangement by overexpression of the non-receptor protein tyrosine kinase p56lck. - Anderson, S J (1992)
The variable region genes of the T cell receptor (TCR) alpha and beta chains are assembled by somatic recombination of separate germline elements. During thymocyte development, gene rearrangements display both an ordered progression, with beta chain formation preceding alpha chain, and allelic exclusion, with each cell containing a single functional beta chain rearrangement. Although considerable evidence supports the view that the individual loci are regulated independently, signaling molecules that may participate in controlling TCR gene recombination remain unidentified. Here we report that the lymphocyte-specific protein tyrosine kinase p56lck, when overexpressed in developing thymocytes, provokes a reduction in V beta--D beta rearrangement while permitting normal juxtaposition of other TCR gene segments. Our data support a model in which p56lck activity impinges upon a signaling process that ordinarily permits allelic exclusion at the beta-chain locus.